2015
DOI: 10.1007/s11103-015-0360-8
|View full text |Cite
|
Sign up to set email alerts
|

Rice WRKY4 acts as a transcriptional activator mediating defense responses toward Rhizoctonia solani, the causing agent of rice sheath blight

Abstract: WRKY transcription factors have been implicated in the regulation of transcriptional reprogramming associated with various plant processes but most notably with plant defense responses to pathogens. Here we demonstrate that expression of rice WRKY4 gene (OsWRKY4) was rapidly and strongly induced upon infection of Rhizoctonia solani, the causing agent of rice sheath blight, and exogenous jasmonic acid (JA) and ethylene (ET). OsWRKY4 is localized to the nucleus of plant cells and possesses transcriptional activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
80
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 77 publications
6
80
0
Order By: Relevance
“…To determine if OsWRKY80 has transcriptional activation activity, we fused the full-length OsWRKY80 in frame to the GAL4 DNA binding domain in the pGBKT7 vector and transformed into yeast strain AH109. Empty vector pBD and pBD-WRKY4 (Wang et al 2015) were used as negative and positive control, respectively. The results showed that cells transformed with pBD-WRKY80 grew well on synthetic SD-Trp-Ade-His selection media (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To determine if OsWRKY80 has transcriptional activation activity, we fused the full-length OsWRKY80 in frame to the GAL4 DNA binding domain in the pGBKT7 vector and transformed into yeast strain AH109. Empty vector pBD and pBD-WRKY4 (Wang et al 2015) were used as negative and positive control, respectively. The results showed that cells transformed with pBD-WRKY80 grew well on synthetic SD-Trp-Ade-His selection media (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To date, at least 13 Oryza sativa WRKY ( OsWRKY ) genes are known to positively regulate rice resistance against pathogens, such as Magnaporthe oryzae , Rhizoctonia solani and Xanthomonas oryzae pv oryzae ( Xoo ) (Cheng et al 2015; Wang et al 2015; Choi et al 2015; Hwang et al 2016). For instance, OsWRKY13 activates SA-dependent defense response whereas suppresses JA-dependent response, in mediating rice defense response to bacterial blight and fungal blast pathogens (Qiu et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This gene is also associated with the activation of several genes, including jasmonic acid (JA) biosynthesis genes and pathogenesisrelated genes (Peng et al 2012). A recent study shows that OsWRKY4, in Group I, functions as a transcriptional activator of genes important in the defense response to R. solani (Wang et al 2015). More recently it is reported that OsWRKY6 functions as a positive regulator in defense response (Hwang et al 2011;Choi et al 2015).…”
Section: Introductionmentioning
confidence: 99%